Low-Level Vagus Nerve Stimulation Reverses Obstructive Sleep Apnea-Related Atrial Fibrillation by Ameliorating Sympathetic Hyperactivity and Atrial Myocyte Injury - Guo, Yankai; Xiaokereti, Jiasuoer; Meng, Qingjun; Cao, Guiqiu; Sun, Huaxin; Zhou, Xianhui; Zhang, Ling; Tang, Baopeng (Frontiers in Physiology, 2021)
Background Previous studies have proved that low-level vagus nerve stimulation (LLVS) could suppressed acute obstructive sleep apnea (OSA) associated atrial fibrillation (AF). Objective This study mainly investigates the underlying electrophysiological, neural and cardiomyocyte injury mechanisms on acute OSA-induced AF, and testify whether LLVS can attenuate or reverse these remodeling. Methods and results Eighteen mongrel dogs received endotracheal intubation under general anesthesia and randomly divided into three groups: the OSA group (simulated OSA with clamping the trachea cannula at the end of expiration for 2 mins followed ventilation 8 mins, lasting 6 hours, n =6), the OSA+LLVS group (simulated OSA plus LLVS, n =6), the control group (sham clamping the trachea cannula without stimulation, n =6). In OSA+LLVS group, the atrial effective refractory period was significantly lengthen while the sinus node recovery time and AF duration were evidently decreased after the 4th hour, and the expression level of Cx40 and Cx43 was significantly increased compared to the OSA group. Norepinephrine, TH, and ChAT were significantly decreased in the OSA+LLVS group compared with the OSA group. The mitochondrial swelling, cardiomyocyte apoptosis, and glycogen deposition, and higher concentration of TNF-α, IL-6 could be observed in the OSA group, and the LLVS could inhibit the structural remodeling and the expression of inflammatory cytokines. Conclusion LLVS could decrease the inducibility of AF might partly by ameliorating sympathetic hyperactivity and atrial myocyte injury after acute OSA-induced AF.